The effect of corporate social responsibility, customer-company identification and trust on satisfaction in banking sector / Wan Nur Hidayah Wan Ahmad Hidhir - Ahmad Hidhir, Wan Nur Hidayah (Faculty of Business and Management, 2018)
The overall objective of this study is to identify association between Corporate Social Responsibility (CSR) with customer satisfaction towards banking sector, to identify association between Customer-Company Identification (CCI) with customer satisfaction towards banking sector, to identify association between trust with customer satisfaction towards banking sector and to identify most influential factor of independent variable towards dependent variable. Simple random sampling was used in this study and structured questionnaire were used and distributed to 136 respondents whom are staff in UiTM Cawangan Melaka Kampus Bandaraya. Results from data analysis were based on SPSS version 20. The quantitative type of data was used for the purpose of the study. This research thus proposes three independent variable which are corporate social responsibility (CSR), customer-company identification (CCI) and trust and also to investigate these relationship and effect on customer satisfaction on banking sector. The results show that all of these variables have positive relationships with customer satisfaction in banking sectors.